Old Acquaintances and Novel Complex Structures for the Ni(II) and Cu(II) Complexes of bis-Chelate Oxime–Amide Ligands - Carla Bazzicalupi; Craig Grimmer; Igor Vasyl Nikolayenko (Molecules, 2024)
In the process of systematically studying the methylhydroxyiminoethaneamide bis-chelate ligands with polymethylene spacers of different lengths, L1–L3, and their transition metal complexes, a number of new Ni(II) and Cu(II) species have been isolated, and their molecular and crystal structures were determined using single-crystal X-ray diffraction. In all of these compounds, the divalent metal is coordinated by the ligand donor atoms in a square-planar arrangement. In addition, a serendipitously discovered new type of neutral Ni(II) complex, where the propane spacer of ligand L2 underwent oxidation to the propene spacer, and one of the amide groups was oxidised to the ketoimine, is also reported. The resulting ligand L2′ affords the formation of neutral planar Ni(II) complexes, which are assembled in the solid state on top of each other, and yield two polymorphic structures. In both structures, the resulting infinite, exclusively parallel metal ion columns in ligand insulation may serve as precursor materials for sub-nano-conducting connectors. Overall, this paper reports the synthesis and characterisation of seven new anionic, cationic, and neutral Ni(II) and Cu(II) complexes, their crystal structures, as well as experimental and computed UV–Vis absorption spectra for two structurally similar Ni(II) complexes, yellow and red.